Quantum crystallography. Issue 6 (27th March 2017) - Grabowsky, Simon; Genoni, Alessandro; Bürgi, Hans-Beat
Abstract : Quantum crystallography combines quantum chemistry and experimental diffraction or scattering to provide both enhanced wavefunctions and charge densities. Abstract : Approximate wavefunctions can be improved by constraining them to reproduce observations derived from diffraction and scattering experiments. Conversely, charge density models, incorporating electron-density distributions, atomic positions and atomic motion, can be improved by supplementing diffraction experiments with quantum chemically calculated, tailor-made electron densities (form factors). In both cases quantum chemistry and diffraction/scattering experiments are combined into a single, integrated tool. The development of quantum crystallographic research is reviewed. Some results obtained by quantum crystallography illustrate the potential and limitations of this field.